Renewing neighbourhoods work, enterprise and governance - Syrett, Stephen 1962-; North, David ca. 20./21. Jh (Policy Press, 2008)
Jobs and enterprise are critical to creating viable neighbourhoods. Yet much recent policy activity aimed at the regeneration of deprived neighbourhoods has had only a marginal impact on the economic challenges presented by areas of concentrated disadvantage. This book directly addresses the economic development issues central to neighbourhood renewal, drawing on the authors' original research and wide-ranging analysis of recent academic theory and policy practice. Their critical examination of the economic problems of deprived areas, and the range of employment and enterprise-related policy initiatives and governance arrangements that have attempted to address them, offers informed insights into what does and what does not work. Through its topical focus on issues of work and enterprise in deprived neighbourhoods, "Renewing neighbourhoods" goes to the heart of much current policy practice that seeks to combine concerns of economic competitiveness with those of social exclusion. It will be essential reading for academics, practitioners and policy makers working in the fields of urban regeneration, neighbourhood renewal and local and regional economic development. It will also be a key text for students of urban studies, planning, social policy, human geography and related disciplines